2020
DOI: 10.1038/s41467-020-18444-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti-CD147 chimeric antigen receptors targeting hepatocellular carcinoma

Abstract: Chimeric antigen receptor (CAR) therapy is a promising immunotherapeutic strategy for treating multiple refractory blood cancers, but further advances are required for solid tumor CAR therapy. One challenge is identifying a safe and effective tumor antigen. Here, we devise a strategy for targeting hepatocellular carcinoma (HCC, one of the deadliest malignancies). We report that T and NK cells transduced with a CAR that recognizes the surface marker, CD147, also known as Basigin, can effectively kill various ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 81 publications
2
75
0
Order By: Relevance
“…In another study, T and NK cells transduced with a CD147-specific CAR could efficiently eliminate several HCC cell lines in vitro and HCC tumors in xenograft murine models. The use of logic-gated (log) GPC3-synNotch-inducible CD147-CAR for reducing on-target/off-tumor toxicity in HCC showed that LogCD147-CAR could selectively eliminate dual antigen (GPC3-positive CD147-positive), but not single antigen (GPC3-negative CD147-positive) positive HCC cells without any serious on-target/off-tumor toxicity in a human CD147 transgenic murine model ( 100 ). Besides, respecting the TGF-β capability to inhibit NK cell function, Wang and his coworkers genetically modified NK-92 cells to present a chimeric receptor with TGF-β type II receptor extracellular and transmembrane domains associated with intracellular domain of NKG2D, termed as TN chimeric receptor.…”
Section: Car Nk Cells In Solid Tumorsmentioning
confidence: 99%
“…In another study, T and NK cells transduced with a CD147-specific CAR could efficiently eliminate several HCC cell lines in vitro and HCC tumors in xenograft murine models. The use of logic-gated (log) GPC3-synNotch-inducible CD147-CAR for reducing on-target/off-tumor toxicity in HCC showed that LogCD147-CAR could selectively eliminate dual antigen (GPC3-positive CD147-positive), but not single antigen (GPC3-negative CD147-positive) positive HCC cells without any serious on-target/off-tumor toxicity in a human CD147 transgenic murine model ( 100 ). Besides, respecting the TGF-β capability to inhibit NK cell function, Wang and his coworkers genetically modified NK-92 cells to present a chimeric receptor with TGF-β type II receptor extracellular and transmembrane domains associated with intracellular domain of NKG2D, termed as TN chimeric receptor.…”
Section: Car Nk Cells In Solid Tumorsmentioning
confidence: 99%
“…An open label early phase I clinical trial has started to recruit patients with recurrent GBM to test the safety, tolerance and efficacy of treatment with CD147-specific CAR T cells (NCT04045847). While CD147 is overexpressed on malignant cells, it is still expressed at a low level on various normal tissues such as epithelial and endothelial cells, and brain and heart tissue ( Riethdorf et al, 2006 ; Liao et al, 2011 ; Tseng et al, 2020 ). Therefore, there is a concern that CD147-specific CAR T cells may cause on-target off-tumor side effects.…”
Section: Targets Of Car T Cell Therapy In On-going Clinical Trialsmentioning
confidence: 99%
“…Another marker of interest is CD147 (also known as basigin), which is present at low levels in different cell types, including hematopoietic, epithelial, and endothelial, and is found highly expressed in a variety of cancer cells. Recently, it was shown that CAR-T cells recognizing CD147 could effectively kill HCC cell lines in vitro and inhibit xenograft growth in mouse models 286 and are now being tested in a phase 1 clinical trial (NCT03993743). Meanwhile, EpCAM-recognizing CAR-T cells are being tested in clinical trials for the treatment of epithelial cancers, with two of them having a particular focus on HCC (NCT02729493 and NCT03013712), while one ongoing phase 1/2 clinical trial is aiming to test the efficacy of anti-MET cells in HCC and other malignancies (NCT03638206).…”
Section: Adoptive Cell Therapy (Act)mentioning
confidence: 99%